2011
DOI: 10.1016/j.paid.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Mate-selection and the Dark Triad: Facilitating a short-term mating strategy and creating a volatile environment

Abstract: a b s t r a c tThe current study (N = 242) seeks to establish the relationship between traits known collectively as the Dark Triad -narcissism, psychopathy, Machiavellianism -and mating standards and preferences. Using a budget-allocation task, we correlated scores on the Dark Triad traits with mate preferences for a longterm and short-term mate. Men scoring high on the Dark Triad may be more indiscriminate than most when selecting for short-term mates in order to widen their prospects. Furthermore, those high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
107
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 43 publications
(67 reference statements)
11
107
2
4
Order By: Relevance
“…In confirmation of the context-specific value of the Dark Triad traits suggested by evolutionary psychologists (Jonason et al, 2009(Jonason et al, , 2011, both sexes found advertisements with low levels of the traits more desirable as spouses, and advertisements with high levels of the traits as more desirable one-night stand partners. Long-term partnerships are characterized by high levels of mutual investment (Buss & Schmitt, 1993), essential for bi-parental care (Fisher, 1994), which may require ongoing amicability.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In confirmation of the context-specific value of the Dark Triad traits suggested by evolutionary psychologists (Jonason et al, 2009(Jonason et al, , 2011, both sexes found advertisements with low levels of the traits more desirable as spouses, and advertisements with high levels of the traits as more desirable one-night stand partners. Long-term partnerships are characterized by high levels of mutual investment (Buss & Schmitt, 1993), essential for bi-parental care (Fisher, 1994), which may require ongoing amicability.…”
Section: Discussionmentioning
confidence: 63%
“…Prior work on the role the Dark Triad traits play in mating psychology have focused on existing couples (Smith et al, 2014), other aspects of mating psychology (e.g., mate retention; Jonason, Li et al, 2010), or on mate preferences (Jonason et al, 2011). As mate choice might differ from mate preferences (Todd et al, 2007), we wanted to ascertain whether those characterized by the Dark Triad traits actively choose homogamous partners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, narcissism may be adaptive in some cases (Paulhus, 1998), as evidenced by its positive links with trait emotional intelligence ), self-esteem (ZeiglerHill, 2006) subjective well-being (Rose & Campbell, 2004), and life expectancy (Jonason, Baughman, Carter, & Parker, 2015). In the mating context, narcissistic individuals are perceived as more attractive and are more successful in acquiring short-term mates than are non-narcissists (Holtzman & Strube, 2010;Jonason, Li, Webster, & Schmitt, 2009;Jonason, Valentine, Li, & Harbeson, 2011).…”
Section: Introductionmentioning
confidence: 99%